Structural subsurface model of Samawa-Diwan area (south of Iraq) - Abed Al-Ridha, Nawal; AL-Sharaa, Ghazi H.; Muhsin, Suhail U. (Iraqi Journal of Science, 2018)
Seismic instantaneous phase attribute was applied for conventional seismic interpretation (structural interpretation) on 3D seismic cube of 1914.72km² of Samawa-Diwan area, located in the south part of Iraq within Muthna governorate. Instantaneous phase section is very important to detect structural and stratigraphic features. Six reflectors represent Upper Jurassic and Cretaceous formations were defined from synthetic seismogram of wells in study area, then picked over seismic cube. Fault boundaries maps for each horizon were drawn depending on horizon contacts then fault planes were constructed. Finally, a 3D structural model was constructed in time domain, then converted to depth domain by using 3D average velocity model. Structurally, 3D models showed that study area affected by two types of normal faults formed a graben appear at west side a long study area, and separated by transverse fault to the north and south parts at Hartha Fn. and deep layers, while Tertiary formations have not affected by any type of faults systems. Also, structural map showed existence of four structural domes which they are Samawa and Diwan folded domes, Samawa south faulted dome and fourth one is new folded dome locates in the northwest of study area. All these features extend in northwest-southeast trend.